PENERAPAN KOMBINASI MODEL PEMBELAJARAN PBL DAN NHT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS X MIPA 6 SMAN 7 BANJARMASIN PADA KONSEP FUNGI - Noorhidayati Noorhidayati; Khairun Nisa Khairun Nisa; Hardiansyah Hardiansyah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. The activity of students of class X MIPA 6 of SMAN 7 Banjarmasin on the learning of the Fungi concept in the 2016/2017 school year is still relatively low, even though their learning outcomes are in accordance with the KKM (≥70). The teacher has implemented various ways to increase student activity. Student activities will affect student learning outcomes. Classroom Action Reseach (CAR) as an effort to improve the quality of teaching and the learning in classroom also indirectly plays an important role in improving the quality of education. This research aimed to improve student activity and learning outcomes, as well as describe the responses of students in class X MIPA 6 of SMAN 7 Banjarmasin in the academic year 2017/2018 on the learning of the Fungi concept through the implementation of a combination of PBL and NHT learning models. Research subjects were 34 students with 14 male students and 20 female students. This research was carried out in 2 cycles with 2 meetings per cycle. This results indicated that student activities that were observed increased from cycle-I (83.5) to cycle-II (89). Cognitive learning outcomes of students assessed through posttest increased from cycle-I (80%) to cycle-II (92%). The learning outcomes of the process were assessed through LKPD, questions and answers about NHT, and the product increased from cycle-I (72.08) to cycle-II (82.70). Affective learning outcomes: 1) character behavior were observed increased from cycle-I (77.74) to cycle-II (92.64), 2) social behavior were observed increased from cycle-I (71.88) to cycle-II (91.84). Psychomotor learning outcomes were observed increased from cycle-I (74.66) to cycle-II (86.03). The response of students to these models showed a positive response (98%). The implementation of a combination of PBL and NHT learning models can improve student activity and learning outcomes on the concept of Fungi.